2004
DOI: 10.1103/physrevb.69.193304
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced oscillatory magnetoresistance as a sensitive probe of the zero-field spin-splitting in high-mobilityGaAs/Alx

Abstract: We suggest an approach for characterizing the zero-field spin splitting of high mobility 2D electron systems, when beats are not readily observable in the Shubnikov-de Haas effect. The zero-field spin splitting and the effective magnetic field seen in the reference frame of the electron are evaluated from a quantitative study of beats observed in radiation-induced magnetoresistance oscillations

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Recently, it was proposed that the radiation-induced oscillatory magnetoresistance can be used as a sensitive probe of the zero-field spin-splitting [182]. The experimental results indicated that the largest Rashba parameter α R can be 30 × 10 −12 eV m [161,163] or even 40 × 10 −12 eV m [165] for InAs and 14 × 10 −12 eV m for GaSb [180] quantum wells, while the smallest Rashba parameter can be negligible [178,183].…”
Section: Electron Spin-orbit Coupling In Nanostructuresmentioning
confidence: 95%
“…Recently, it was proposed that the radiation-induced oscillatory magnetoresistance can be used as a sensitive probe of the zero-field spin-splitting [182]. The experimental results indicated that the largest Rashba parameter α R can be 30 × 10 −12 eV m [161,163] or even 40 × 10 −12 eV m [165] for InAs and 14 × 10 −12 eV m for GaSb [180] quantum wells, while the smallest Rashba parameter can be negligible [178,183].…”
Section: Electron Spin-orbit Coupling In Nanostructuresmentioning
confidence: 95%
“…To shed some light on the physics behind them, a great effort has been made, especially from the experimental side, growing better samples, adding new features and different probes to the basic experimental setup, etc. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Of course the experimental results always mean a real challenge for the existent theoretical models. Thus, a comparison of experiment with theory could help to identify the importance of the invoked mechanisms in these theories.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The spin-orbit strength can be measured in a variety of different experimental setups: 11 In a magnetoresistance measurement via Shubnikov-de Haas oscillations, 7,8,[12][13][14] weak (anti-) localization, 13,[15][16][17] or electron spin resonances in semiconducting nanostructures [18][19][20][21] or quantum dots, 22 or optically via spin relaxation, 23 spin precession, 18 spin-flip Raman scattering, 24 or radiation-induced magnetoresistance oscillations. 25 In this paper, we propose a method for extracting the strength of the Rashba spin-orbit interaction via a charge conductance measurement. This method does not require the use of external magnetic fields or radiation sources.…”
Section: Introductionmentioning
confidence: 99%